정지궤도 위성의 적외선 채널 관측을 이용한 산불과 스모크 동시 모니터링 - 이권호(Kwon-Ho Lee); 김관철(Kwanchul Kim); 이다솜(Dasom Lee); 하종성(Jong-Sung Ha); 김희섭(Heeseob Kim) (한국대기환경학회지(국문), 2024)
Large wildfires have a significant impact on regional air quality and climate. Active fires and smoke emissions are highly variable, making it difficult to determine their impact on air quality. In this study, we present a methodology to derive temporal location information on active fire and smoke using observations from the Advanced Meteorological Imager (AMI) on Geo-KOMPSAT-2A (GK2A). Comparison of the GK2A/AMI observations with Moderate Resolution Imaging Spectroradiometer (MODIS) fire products confirmed that the location of active fires and the area of smoke plumes were well detected within the observation coverage. In March 2022, two large wildfires in eastern South Korea burned an area of more than 250 square kilometers and sent huge smoke plumes up to 20 kilometers over the East Sea, resulting in PM10 and PM2.5 concentrations of up to 910 μg/m3 and 803 μg/m3, respectively, measured at the nearest stations. Therefore, integrated analysis of ground-based and remote sensing observations can play an important role in effectively monitoring wildfire areas and smoke plumes. KCI Citation Count: 1